The Revised Screening Scale for Pedophilic Interests (SSPI–2): Development and Criterion-Related Validation. (October 2017) - Seto, Michael C.; Stephens, Skye; Lalumière, Martin L.; Cantor, James M.
The Screening Scale for Pedophilic Interests (SSPI) is a structured rating scale of four child victim characteristics: number, age, gender, and relationship of victims. Sexual offenders against children who score higher on the SSPI are more likely to be identified as having pedophilic sexual arousal and are more likely to sexually reoffend. Recent research suggests that child pornography offending is a valid and perhaps independent indicator of pedophilia. In this study, we examined whether child pornography offending would add to the criterion-related validity of the SSPI. In the construction sample of 950 offenders with child victims, the SSPI with a fifth item of child pornography (Screening Scale for Pedophilic Interests–2 [SSPI-2]) was significantly associated with phallometrically assessed sexual arousal to children. In a validation sample of 950 offenders with child victims, the SSPI-2 was again related to phallometrically assessed sexual arousal to children, outperforming the original SSPI. We recommend clinicians and researchers use the SSPI-2 as a structured method of assessing pedophilic sexual interests based on offending behavior.